The effect of wind generation on an islanded network based on rotor angle dynamic evaluation - Masoum, Mohammad Sherkat (Engineers Media Pty Ltd., 2014)
The application of wind generation systems to an islanded power station (typicalindustrial application) has not been carefully assessed. In this paper, the utilisation of windgenerators running in parallel to a local power station supplying a large industrial operation(such as mining plants) is reviewed and investigated with emphasis placed on the swing equation.Consideration has been placed on the inertia offered by the power station equipment as well asthe wind generators (in this case 1.5 MW units). Detailed simulations are conducted in order tounderstand the impact doubly-fed induction generator wind generation will have on an islandedpower system with large loads. This information is to be used to determine the limits of windgeneration on such power generation arrangements.